Peter Dorman – Betsy Bryan (eds.), Sacred Space and Sacred Function in Ancient Thebes. Occasional Proceedings of the Theban Workshop. Studies in Ancient Oriental Civilization 61. Chicago, The Oriental Institute Press, 2007, 213 pp., con fotos y mapas. ISBN: 978-1-885923-46-2. U$S 35.00 - Della Casa, Romina (2008)
Fil: Della Casa, Romina. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Departamento de Historia; Argentina